Aplikasi E-Membership dengan Pendekatan Customer Relationship Management (CRM) pada Dialog Koffie Berbasis Mobile - Nabila, Andini; Putri, Raissa Amanda (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The rise of the coffee trend means that coffee shop entrepreneurs must be able to compete with other coffee shops. Dialog Koffie still uses a manual ordering system in its sales process, which causes problems such as duplicate orders and mixed order notes due to the large number of notes. Apart from the ineffectiveness of the ordering system, customers do not get the privilege of coming to Dialog Koffie frequently. This makes shop owners have to provide different services to satisfy their customers. In this case, a different business strategy is needed that has not been used by other coffee shops. Customer Relationship Management (CRM) is a model of approach to customers that is able to solve the problems above. By implementing CRM in the E-Membership application, customer loyalty will also increase because this system provides various features such as viewing menus and promos, place reservations, as well as a point system for every drink purchase, where the points are collected and can be exchanged for the menu the customer wants. The system that has been built can help shop owners maintain good relations between the shop and customers, get as many new customers as possible, and provide satisfactory service to customers by simplifying the ordering system and point exchange system that has been created.